Anodic oxidation of AlMgSi1 — Coatings' mechanical properties, process costs and energy consumption of the oxide formation. (5th January 2016) - Sieber, Maximilian; Scharf, Ingolf; Herold, Franziska; Schmidt, Anja; Böttger, Dagmar; Böttger, Sebastian; Böttger, Eckhard; Götze, Uwe; Lampke, Thomas
Abstract: In recent years, the growing environmental awareness has led to the development of energy-efficient products, for example by the replacement of steel as construction material by aluminium to save weight and thus increase the energy-efficiency of mobile systems. However, to address the energy-efficiency of a product holistically, the energy consumption of the production process also has to be considered. For the anodic oxidation process of the AlMgSi1 aluminium alloy, the influence of the sulphuric acid concentration, the glycolic acid concentration, the electrolyte temperature and current density on coating thickness, hardness, ductility and wear resistance (scratch test), as well as on the consumption of electrical energy and process costs for the oxide coating formation are investigated using a design of experiments (DOE). An analysis of variance (ANOVA) is conducted to assess the significance of the parameters for the coating and process properties. For the considered range of the process parameters a significant enhancement of thickness, hardness and wear resistance of the coatings alters also energy consumption during anodic oxidation and process costs, which are assessed by material flow cost accounting (MFCA). Graphical abstract: Highlights: Anodic oxidation was used for production of oxide coatings on AlMgSi1 alloy. Influence of process parameters on mechanical coating properties was investigated with a design of experiments. Material flow cost accounting was used to assess coating production costs, also considering energy consumption. Any enhancement of coatings' mechanical properties led to increased process costs.